Islamic political parties and the nature of politics in Pakistan. Issue 2 (3rd May 2016) - Nazar, Mudasir
ABSTRACT: The 'war on terror' has not only increased the operation and significance of Islamic parties but also intensified suspicion against them. The lack of comprehensive theoretical research about Islamic parties has further contributed to misunderstanding of their nature and politics. This article theorizes and classifies Islamic parties, especially of Pakistan, and explores their origin, development and nature. The conventional theories of party origin and traditional classifications of political parties are shown to have limited validity in the case of Islamic parties. Rather, the origin and development of Islamic parties is explored through the theoretical construct of historical crisis situation theory, consisting of four crisis situations. Moreover, a new typology of Islamic parties is developed and the Islamic parties are classified on the basis of six variables into three parties: clerical, conservative and Islamist. The exploration of the role of Islamic parties in Pakistan shows that party variables are not only essential to understand their proper nature but also critical to comprehend their politics. Though unanimously categorized as 'Islamic', their politics significantly differ and Pakistan provides a typical case to show the heterogeneous Islamic politics of Islamic parties.